CAUSES OF DENTAL CARIES AND PREVENTIVE MEASURES - Babayeva N.M (TADQIQOTLAR.UZ, 2024)
The objective of this study is to review medical and non medical treatments for prevention of caries. Dental caries is a pathologic process depending on several etiologic factors, which cause the destruction of the dental tissues and produces local and general complications.